Quality of sleep and hypertension in adolescents - Arie Taufansyah P. Nasution; Rafita Ramayati; Sri Sofyani; Oke rRna Ramayani; Rosmayanti Siregar (Paediatrica Indonesiana, 2016)
Background Adolescents with hypertension are at risk of morbidity and mortality due to cardiovascular problems in later life. Hypertension may be influenced by poor quality of sleep, so early detection of hypertension and ensuring good quality of sleep in adolescence is needed.Objective To assess for a possible association between poor sleep quality and hypertension in adolescents.Methods We conducted a cross-sectional study from January to March 2013 in Mustafawiyah Boarding School, Mandailing Natal, North Sumatera. Subjectsâ€™ quality of sleep was assessed by the Pittsburgh Sleep Quality Index (PSQI) questionnaire and their systolic and diastolic blood pressures were measured. Quality of sleep was categorized as either good or poor. Blood pressure was categorized as either normotensive or hypertensive. An association between poor sleep quality and hypertension was analyzed by Chi-square test.Results Two hundred forty adolescents participated in this study, of whom 210 (87.5%) subjects were normotensive and 30 (12.5%) subjects were hypertensive. We found higher systolic blood pressure [114.9 (SD 11.7) vs. 109.5 (SD 10.5) mmHg as well as diastolic blood pressure [74 (SD 9.1) vs. 69.9 (SD 7.5) mmHg in adolescents with poor sleep quality compared to Â those with good sleep quality (P=0.001).Conclusion Poor sleep quality is associated with hypertension in adolescents.